2009
DOI: 10.1111/j.1467-8624.2009.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning in a Natural Language by 8‐Month‐Old Infants

Abstract: Numerous studies over the past decade support the claim that infants are equipped with powerful statistical language learning mechanisms. The primary evidence for statistical language learning in word segmentation comes from studies using artificial languages, continuous streams of synthesized syllables that are highly simplified relative to real speech. To what extent can these conclusions be scaled up to natural language learning? In the current experiments, English-learning 8-month-old infants’ ability to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
268
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(297 citation statements)
references
References 34 publications
10
268
0
4
Order By: Relevance
“…In recent years, such statistical learning has been demonstrated not only in the auditory domain using syllables (Saffran et al 1996;Pelucchi et al 2009) and tones (Saffran et al 1999;Durrant et al 2013), but also in the visual domain using abstract symbols (Fiser and Aslin 2001;Turk-Browne et al 2008). It has been shown in infants (Saffran et al 1996), adults (Saffran et al 1999), and even non-human primates (Hauser et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, such statistical learning has been demonstrated not only in the auditory domain using syllables (Saffran et al 1996;Pelucchi et al 2009) and tones (Saffran et al 1999;Durrant et al 2013), but also in the visual domain using abstract symbols (Fiser and Aslin 2001;Turk-Browne et al 2008). It has been shown in infants (Saffran et al 1996), adults (Saffran et al 1999), and even non-human primates (Hauser et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…People certainly employ statistical learning in procedural tasks, like learning artificial grammars (Pelucchi, Hay, & Saffran, 2009) and motor sequences (Daselaar, Rombouts, Veltman, Raaijmakers, & Jonker, 2003), regardless of whether the features are processed consciously or not. The feature approach is well established in memory research.…”
Section: R Emembering Music Is An Important Partmentioning
confidence: 99%
“…Many accounts of adjacent dependency learning posit that learners track statistical information about the transitions from one unit (e.g., syllable or word) to the next (Romberg & Saffran, 2013;Saffran, Aslin, & Newport, 1996). However, while most studies of adjacent dependencies have found success in a variety of learning scenarios (Pelucchi, Hay, & Saffran, 2009;Saffran et al, 1996; Thompson & Newport, 2007), the studies of non-adjacent dependencies to date have only found learning in limited situations, with some studies reporting success in learning and others reporting failure.(e.g., success: Gómez, 2002;Gómez & Maye, 2005;Romberg & Saffran, 2013; failure: Newport & Aslin, 2004; mixed: Peña, Bonatti, Nespor & Mehler, 2002; Santelmann & Jusczyk, 1998). In…”
mentioning
confidence: 99%